Administrative Efficiency in Official Travel Management: A Literature Review on Bureaucratic Processes and Cost Control in Local Government - Nur Mala Sari; Ulul Albab; Sapto Pramono; Dian Ferriswara (International Forum of Researchers and Lecturers, 2026)
Official travel constitutes a routine yet strategically significant component of local government administration, closely intertwined with bureaucratic processes, public financial management, and accountability arrangements. Despite its operational importance and fiscal visibility, official travel management has received limited integrative attention in the public administration literature, and existing studies remain fragmented across procedural, financial, and governance perspectives. This article addresses this gap by providing a comprehensive literature review on administrative efficiency in official travel management within local governments, with particular attention to bureaucratic processes and cost control mechanisms. Adopting a narrative–analytical literature review design, the study employs a state-of-the-art and theory-driven synthesis of recent peer-reviewed scholarship in public administration, public financial management, governance, and related fields. The analysis integrates thematic and conceptual synthesis techniques to identify recurring patterns, relationships among key concepts, and unresolved issues in the literature. The findings reveal consistent patterns of procedural inefficiency, including administrative burden, complex approval chains, and process fragmentation, which persist even under formal cost control and accountability systems. The review further demonstrates that compliance-oriented financial controls often secure fiscal conformity without necessarily improving administrative efficiency, particularly when misaligned with bureaucratic workflows and constrained by limited administrative capacity. Governance and accountability mechanisms enhance transparency and oversight but frequently prioritize answerability over performance learning, thereby legitimizing inefficiencies rather than resolving them. By synthesizing insights from Administrative Efficiency Theory, Public Financial Management, Bureaucratic Process Theory, Administrative Capacity Theory, and Governance and Accountability perspectives, this article advances an integrative conceptual framework that explains efficiency outcomes as systemic products of interacting institutional dimensions.